Analisis Level Kinerja Expert Melalui Kemampuan Berpikir Kritis Siswa (Interpretasi, Analisis , Evaluasi, Inferensi ): Analysis of Expert Performance Levels Through Students' Critical Thinking Ability (Interpretation, Analysis, Evaluation, Inference) - Indah Rahayu Panglipur; Eric Dwi Putra (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
Each individual has different thinking skills that are influenced by various factors. Students can think critically with skills through the results of analyzing and verifying truth actively and effectively. The purpose of this study was to determine the level of performance of student experts through critical thinking skills based on mathematical abilities. There is a level of performance (performance) consisting of 4 levels set by Exemplar. The four levels are Beginners, Internships, Practitioners, and Experts. The method used is qualitative research with a descriptive approach. the results of this study that the level of performance of expert students have different levels of critical thinking skills based on the indicators achieved. Students who have high abilities meet all levels of Expert's performance even though there is one indicator that has not been achieved perfectly. Whereas in students with moderate abilities there are 2 indicators that are not fulfilled and low-ability students do not meet all indicators but there are indicators that appear even though not all.